Trade Reforms of Uncertain Duration and Real Uncertainty : A First Approximation - Calvo, Guillermo (IMF Working Papers; Working Paper, 1994)
This paper examines trade reforms of uncertain duration undertaken in economies subject to real foreign and domestic shocks. These reforms induce consumption and import booms regardless of whether they succeed or fail and of the degree of intertemporal elasticity of substitution. If tariff revenue is rebated, a recession follows the boom, but without rebates a boom or a recession may follow depending on the outcome of the reform. Consumption fluctuations reflect imperfect credibility and real shocks, and the credibility component depends on the mean and risk of real asset returns. Thus, observed booms are a noisy signal of imperfect credibility. Quantitatively, lack of credibility produces sizable consumption cycles, but generally smaller than those induced by real disturbances.